Spleen morphometry under the impact of laproxides in experiment - Avilova, Olga (Морфологія / Morphologia / Morfologìâ, 2017)
In subacute experiment were uncovered organometric alterations of the matured male rat’s spleen after the administration of 1/10, 1/100 LD50 of polyether – tryglycidyl ether of polyoxypropylene triol. Rapid technology growth and its implementation in all spheres of the people’s lives dictates the need for thorough study of the influence of different chemicals on human's health. This study was undertaken to elucidate the structural changes that occur in the matured rats’ spleen experimentally induced by selected xenobiotic, exactly the linear dimensions and the weight of the rodents spleen. Were used morphometric, mathematical and statistical methods. Revealed changes of morphologiс data in comparison to control data shows high reactivity of the spleen in response to the induced xenobiotic. These data are useful for understanding the toxicological effects induced by investigated polyether and provide evidence for the mechanism of toxicity of the agent and how it impacts the immune system.